Betulinic acid: A natural promising anticancer drug, current situation, and future perspectives. Issue 12 (19th September 2022) - Aswathy, Maniyamma; Vijayan, Ajesh; Daimary, Uzini D.; Girisa, Sosmitha; Radhakrishnan, Kokkuvayil V.; Kunnumakkara, Ajaikumar B.
Abstract: Natural products serve as the single most productive source for the discovery of drugs and pharmaceutical leads. Among the various chemicals derived from microbes, plants, and animals, phytochemicals have emerged as potential candidates for the development of anticancer drugs due to their structural diversities, complexities, and pleiotropic effects. Herein, we discuss betulinic acid (BA), a ubiquitously distributed lupane structured pentacyclic triterpenoid, scrutinized as a promising natural agent for the prevention, suppression, and management of various human malignancies. Ease of availability, common occurrences, cell‐specific cytotoxicity, and astonishing selectivity are the important factors that contribute to the development of BA as an anticancer agent. The current review delineates the mechanistic framework of BA‐mediated cancer suppression through the modulation of multiple signaling pathways and also summarizes the key outcomes of BA in preclinical investigations.